Semiotics across Cultures: An Analysis of Shop Signs in American and Iraqi Contexts - Alzubaidi, Nassir .A. G; Alrawi, Marwa Firas Abdullah (Al-Adab Journal, 2018)
This study examines the textual and visual resources of shopfront advertising signs in two different linguistic and cultural contexts, namely, American English and Iraqi Arabic from a semiotics perspective. A multi-analytic semiotics model has been used to examine forty Iraqi and American café and restaurant signs, divided equally into twenty signs for each language. The corpus analysis has revealed that the verbal and visual resources work in parallel in the shop advertising discourse of the two linguistic landscapes under investigation. That is, the discourse of shop advertising signs of the two linguistic landscapes generally tends to use the same textual and visual resources. Moreover, American and Iraqi advertising shop signs are laden with the socio-cultural practices and assumptions of the American and Iraqi societies. Finally, a number of conclusions are presented.